Identifikasi Worldview dalam Ilmu Pengetahuan Barat Kontemporer menurut Syed Muhammad Naquib Al Attas - Usmanul Hakim; Winda Roini (Universitas Darussalam Gontor, 2019)
This article will discuss the characteristics of the Western worldview expressed by Al Attas, which has become the identity of contemporary science. In the formulation of Islamization of Contemporary Knowledge, Al Attas proposed that one of the Islamization stages was rejecting the key concept (worldview) of the West which became the core of contemporary Science. Here, then this article has an interest in discussing the characteristics of the Western worldview. The discussion will be carried out through contain analysis by tracing various works of Al Attas which contain the formulation of Islamization, including “Islam and Secularism.” The research result of the paper is that Al Attas mentions that there are 5 characteristics of the Western worldview, namely: acceptance of rationalism, dualism, humanism, secularism and making the tragedy becoming reality. In the formulation of the Al Attas Islamization process these five characteristics must be identified in every contemporary science and then removed.